Choices in surgical contraception: A view on the relationship between technique and person - del Río Fortuna, Cynthia (2009)
Contraceptive practices can be anthropologically approached as technical activities taking place in people's everyday life. To study their choice we must consider the wider social and symbolic context, involving "non-technical" aspects. Based on an ethnographic study carried out in an obstetrician public service in Buenos Aires, this article addresses the relationship between technique and person-building in the case of female surgical contraception from the perspective of health professionals. We examine the practices and representations by which these professionals regulate the access to that practice, which allows  us to identify ways of biomedic definition and intervention of female bodies.